Method of Graphs for Balancing of Chemical Equations. Teaching Guidelines - Georgi Gachev (Педагогически форум)
The method of graphs is a new and relatively easy way to balance chemical equations. With its help, complex chemical equations can be solved without computing devices. The method is based on an algorithm with simple rules, which significantly reduces the probability of making mistakes. The whole balancing process is entertaining and resembles solving a puzzle. However, in order for the graph method to be applied effectively, some experience and in-depth study are required.